Effects of phenolic acids on tetramethylpyrazine formation via room temperature spontaneous ammoniation of acetoin - Hui Xu; Xuanrui Chen; Qianqian Zhang; Zhizhi Yang; Jingjing Tian; Qihe Chen; Jicheng Chen (Food Chemistry: X)
In this study, we aim to investigate the effects of phenolic acids on tetramethylpyrazine (TTMP) formation in low-temperature environments and discuss its possible mechanism. The results demonstrate that TTMP formation kinetics via acetoin (ACT) ammonification was determined to be pseudo-zero-order reaction, which transitions to a pseudo-first-order kinetic model upon high gallic acid concentrations. The TTMP formation in samples spiked with phenolic acids was significantly higher than the control group. The response surface results that the production of TTMP increases with the extension of time align with the TTMP content trend in vinegar aging. At pH 7.0, TTMP formation was 56 and 70 times higher than at pH 3.0 and pH 11.0, respectively. The findings indicate that phenolic acids can alter reactive imine intermediates associated with the formation of pyrazinyl radicals. This study provides valuable insights into enhancing the characteristic pyrazine flavor and improving quality control in fermented foods.